The archbishop of Mexico, Lanciego Eguilaz, faced with the problems of indoctrination of the Indians - Aguirre Salvador, Rodolfo (2021)
A central concern of the Archbishop of Mexico José Lanciego Eguilaz was the deficiency that the Indians had in the knowledge of Christian doctrine, considering that this endangered the salvation of their souls. The Tridentine Church and the provincial councils entrusted this task to the priests, who, however, did not always fulfill it. Then, the archbishop issued short and medium-term measures to solve the problem: decrees for each parish or doctrine, reinforcement in the training of future priests and a parish  reorganization. In this way, the prelate dedicated himself to improving the parochial instances for a better teaching of the doctrine to the Indians.